Prevalência e fatores associados à hanseníase entre mulheres privadas de liberdade no Brasil - Parente, Eriza de Oliveira (2021)
The prison population is considered a fundamental group for the control of leprosy, since prisons are places that present environmental and social conditions that favor transmission and illness. This study aimed to estimate the prevalence of leprosy in Brazilian female prisoners and to identify factors associated with the disease. Methods: This cross-sectional study explored the prevalence and factors associated with leprosy among Brazilian female prisoners and was carried out between 2014 and 2015 in 15 Brazilian female prisons. Data from 1327 women were collected through Computer-Assisted Self-Interview and dermatological and neurological examination to identify suspected leprosy. Results: The mean age was 33.4 years. Suspicion of leprosy was identified in 5.1% of women in prison, and the lifetime self-reported prevalence was 7.5%. The variables associated with self-reported leprosy throughout life were: women imprisoned once, twice as likely to have leprosy (95%CI: 1.2 - 3.5); white women were 1.4 times more likely to have leprosy than non-white women (95% CI: 1.1 - 1.8); women who knew someone with leprosy were 1.9 times more likely to have leprosy (95%CI: 1.1 - 3.3); and women who shared a cell with 11 or more women were 2.5 times more likely to have leprosy than women who shared a cell with two or fewer people (95% CI: 1.1 - 5.9). Conclusions: A lifetime self-report of leprosy among female inmates in Brazil was more than 100 times higher than that found in a Brazilian cohort of the general population. These values show the extreme vulnerability of this population generated by pre-incarceration poverty, as well as the potential for transmission in prison.